Antifungal Drug Susceptibility Profile of Candida kefyr Isolated from Clinical Samples and Dairy Products - Zahra Zareshahrabadi; Samin Khaliji; Maryam Roudbari; Kamiar Zomorodian (Canadian Journal of Infectious Diseases and Medical Microbiology)
Exploring drug susceptibility is a critical endeavor in the scientific community, setting the stage for advancements in understanding and combating various pathogens. Candida kefyr has emerged as a significant pathogen, particularly affecting immunocompromised individuals with hematologic malignancies and HIV/AIDS conditions. This study aimed to assess the antifungal susceptibility profile of Candida kefyr isolates obtained from clinical samples and dairy products. A total of 134 Candida kefyr yeast isolates were retrieved from three distinct groups: (1) healthy individuals (n = 41), (2) patients (n = 24) including hematologic malignancy (n = 9), HIV/AIDS (n = 7), and diabetes (n = 8), (3) dairy products (milk, yogurt, and cheese, n = 69) stored at −70°C in the Shiraz University of Medical Science. All Candida kefyr isolates were previously identified using conventional and molecular methods. Susceptibility to antifungal drugs, including caspofungin, fluconazole, itraconazole, voriconazole, and amphotericin B, was determined using the microdilution method following CLSI-M27-A3 protocols, with results interpreted according to CLSI-M27-S4 guidelines. The study emphasizes the clear variation in antifungal susceptibility testing of Candida kefyr strains when compared across different groups, including patients, healthy people, and dairy products. According to the results, across all groups, a high minimum inhibitory concentration of fluconazole is evident, and healthy individuals show the highest minimum inhibitory concentration geometric means (4.0681). Also, 79.1% of the isolates were wild type to amphotericin B, with the lowest minimum inhibitory concentration compared to other antifungals tested. This suggests that amphotericin B was more effective against Candida kefyr. These findings showed fewer susceptibilities of Candida kefyr to both triazole and echinocandin classes of antifungal agents. Additionally, it is noteworthy that individuals without medical conditions exhibited higher minimum inhibitory concentration rates to these antifungal agents in comparison to those with underlying health conditions. Consequently, timely diagnosis and appropriate therapeutic interventions emerge as imperative in the effective management of candidiasis cases.